Mapping News Visualization Pattern on Katadata.id and Tirto.id - Veronika Veronika; Adi Wibowo Octavianto; Aditya Heru Wardhana (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
This study addresses the research gap in understanding the types and patterns of visualization used in Covid-19 infographics. By analyzing infographics from popular media platforms in Indonesia, such as Katadata.co.id and Tirto.id, this research aims to fill the existing gap and find visual trends and preferences relevant to health communication. The theoretical framework draws upon concepts from visual communication, information design theory, and health communication. Using a qualitative approach and content analysis techniques, the study examines a sample of infographics from the aforementioned media platforms, categorizing the visualization and showing key trends and preferences. The findings reveal that both media outlets predominantly utilize illustrations, graphics, and text elements rather than charts. Bar graphs and column charts are the most widely used chart types, with Katadata.co.id showing higher frequency of chart elements compared to Tirto.id. Additionally, Katadata.co.id presents a greater number of interactive charts. The colors commonly employed for charts include blue, yellow, orange, and brown. However, the study does not delve into underlying reasons for these visual trends, whether they stem from specific visual strategies employed by the media or are influenced by other factors. The research findings contribute to the development of visually appealing and easily understandable infographics for policymakers and graphic designers.